Using Simulation and Cultural Competency skill to improve quality care to patients in Saudi Arabia - Moussa, Fatchima L (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2018)
AbstractThis paper examines the need for nurses in Saudi Arabia to develop a cultural competency so that they can eliminate healthcare disparity among diverse patients.  As the Kingdom contains many different peoples of various ethnic origins, it is important that nurses be able to demonstrate empathy towards and knowledge of these patients’ cultures.  Simulation is a practice that can promote the acquisition of cultural competency among nursing students.  Both low-fidelity and high-fidelity simulation exercises can be helpful in this regard.  This paper discusses why simulation is an effective tool, various transcultural nursing models that may be applied, and how simulation can enable students to obtain their cultural competency.